Maqasid Shariahs View and its Solution on Foreign Debt in Indonesia - Nurizal Ismail; Baiq Rosmala Dewi (Global Review of Islamic Economics and Business, 2014)
This study entitled Maqasid Shariahs View and Its Solution on Foreign Debt in Indonesia, aims to know the concept of debt from Islamic perspective and to analyze current issues foreign debt in Indonesia. Since economic crisis happened in European countries,Indonesia needs to be more careful in considering the impacts of the crisis. One of the causes was because of the high level of interest of the debts. It made most of crisis happened in many countries hard to pay back their debts. Therefore, it is needed to know how Islamic principles see the concept of debt and give the solution to the problem of debt by using Maqasid's approach. It can give comprehensive solution to the debt because it covers five dimensions: religion, self, intellect, family and wealth, which are very important in human life to attain the happiness and welfare on earth. The study will conclude with some suggestions for futureresearch.